Exogenous L-glutathione improves vitrification outcomes in murine preimplantation embryos - Abdul Rahman, Nor Shahida; Mohamed Noor Khan, Nor Ashikin; Eshak, Zolkapli; Sarbandi, Mimi Sophia; Mohammad Kamal, Aqila Akmal; Abd Malek, Mastura; Abdullah, Fathiah; Abdullah, Maizaton Atmadini; Othman, Fezah (Multidisciplinary Digital Publishing Institute, 2022)
Vitrification is an important tool to store surplus embryos in assisted reproductive technology (ART). However, vitrification increases oxidative damage and results in decreased viability. Studies have reported that L-glutathione (GSH) supplementation improves the preimplantation development of murine embryos. Glutathione constitutes the major non-protein sulphydryl compound in mammalian cells, which confers protection against oxidative damage. However, the effect of GSH supplementation on embryonic vitrification outcomes has yet to be reported. This study aims to determine whether GSH supplementation in culture media improves in vitro culture and vitrification outcomes, as observed through embryo morphology and preimplantation development. Female BALB/c mice aged 6–8 weeks were superovulated through an intraperitoneal injection of 10 IU of pregnant mare serum gonadotrophin (PMSG), followed by 10 IU of human chorionic gonadotrophin (hCG) 48 h later. The mated mice were euthanized by cervical dislocation 48 h after hCG to harvest embryos. Two-cell embryos were randomly assigned to be cultured in either Group 1 (GSH-free medium), Group 2 (GSH-free medium with vitrification), Group 3 (0.01 mM GSH-supplemented medium), or Group 4 (0.01 mM GSH-supplemented medium with vitrification). Non-vitrified (Groups 1 and 3) and vitrified (Groups 2 and 4) embryos were observed for morphological quality and preimplantation development at 24, 48, 72, and 96 h. In the non-vitrified groups, there were significant increases in the number of Grade-1 blastocysts in GSH cultures (p < 0.05). Similarly, in the vitrified groups, GSH supplementation was also seen to significantly increase blastocyst formation. Exogenous GSH supplementation resulted in a significant increase in intracellular GSH, a release of cytochrome c from mitochondria, and a parallel decrease in intracellular reactive oxygen species (ROS) levels in vitrified eight-cell embryos (p < 0.05). GSH supplementation was shown to upregulate Bcl2 expression and downregulate Bax expression in the vitrified preimplantation embryo group. The action of exogenous GSH was concomitant with an increase in the relative abundance of Gpx1 and Sod1. In conclusion, our study demonstrated the novel use and practical applicability of GSH supplementation for improving embryonic cryotolerance via a decrease in ROS levels and the inhibition of apoptotic events by improvement in oxidative status.